MiTE: Program Penyunting Topologi Jaringan untuk Pembelajaran SDN - Muhammad Fajar Sidiq; Akbari Basuki; Didi Rosiyadi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Software-defined networking (SDN) is a network programmability concept that separates the control plane from the data plane by proposing a centralized control plane called a controller. Thus, network administrators are able to program the entire networks and their components via the controller. However, learning SDN is challenging due to its complex network setup and the different types of SDN networks such as OpenFlow, and P4. To ease the learning curve, the use of network emulation and a graphical-based network editor is necessary. This paper discusses the implementation of such an application, called MiTE. It satisfies both requirements: a visual network editor enforced with a configuration generator for emulation purpose. We evaluate the program by implementing IP routing cases for both, OpenFlow-based and P4-based networks. The result shows that both cases can be created easily by using a mouse command. The program has more interactive user interface while the created topologies are more informative. Compared to similar applications, our proposed application has better support for a wider range of SDN networks (Openflow and P4), fine-grain network configuration, and a more informative user interface.